2021
DOI: 10.22159/ajpcr.2021.v14i9.42661
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Approach on Action and Mechanism of Bromelain in Hepatocellular Carcinoma

Abstract: Objective: The objective of the study was to understand biomolecular interactions of Bromelain and its networking with p53 and β-catenin by a computational method of analysis in Hepatocellular carcinoma (HCC) condition. Methodology: The protein interaction partners for p53 and β-catenin involved in the progression of HCC were collected from National Center for Biotechnology Information. We collected data points and standardized the data points for our data analysis from the public database. We used Cytoscape 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…These byproducts are inexpensive raw materials used for high-value-added product formation. Previous studies have reported that the byproducts, particularly pineapple peels and cores (PPC), possess high contents of numerous biodegradable substances, including phenolic compounds, vitamins, minerals, proteolytic enzymes, sugars, and crude fibers, that provide beneficial antioxidants, antimicrobial and anti-inflammatory health effects 39 41 . Thus, PPC is considered a promising nutritional material for increasing the valuable components of functional products.…”
Section: Introductionmentioning
confidence: 99%
“…These byproducts are inexpensive raw materials used for high-value-added product formation. Previous studies have reported that the byproducts, particularly pineapple peels and cores (PPC), possess high contents of numerous biodegradable substances, including phenolic compounds, vitamins, minerals, proteolytic enzymes, sugars, and crude fibers, that provide beneficial antioxidants, antimicrobial and anti-inflammatory health effects 39 41 . Thus, PPC is considered a promising nutritional material for increasing the valuable components of functional products.…”
Section: Introductionmentioning
confidence: 99%